2014
DOI: 10.1080/13607863.2014.967174
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between depression and frailty syndrome: a systematic review

Abstract: Studies on the causal relationship between the two syndromes are clearly necessary in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
149
1
13

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 185 publications
(179 citation statements)
references
References 73 publications
16
149
1
13
Order By: Relevance
“…They found that a multi-domain frailty measurement based on the CGA was more useful than frailty identified by the modified PF criteria in predicting postoperative complications, although both frailty scales were predictive of mortality rate. Thus, even though the physical phenotype of frailty is less time-consuming than the CGA assessment it does not necessarily identify remediable conditions such as malnutrition and depression (Buigues et al, 2014), that can be optimized preoperatively (although both these factors are linked to frailty in a subpopulation of frail older individuals). Afilalo et al (2012) compared the ability of four frailty scales to predict postoperative complications and mortality in patients undergoing coronary artery bypass and/or valve surgery.…”
Section: Comparison Of Different Tools For Measuring Frailty Syndromementioning
confidence: 96%
“…They found that a multi-domain frailty measurement based on the CGA was more useful than frailty identified by the modified PF criteria in predicting postoperative complications, although both frailty scales were predictive of mortality rate. Thus, even though the physical phenotype of frailty is less time-consuming than the CGA assessment it does not necessarily identify remediable conditions such as malnutrition and depression (Buigues et al, 2014), that can be optimized preoperatively (although both these factors are linked to frailty in a subpopulation of frail older individuals). Afilalo et al (2012) compared the ability of four frailty scales to predict postoperative complications and mortality in patients undergoing coronary artery bypass and/or valve surgery.…”
Section: Comparison Of Different Tools For Measuring Frailty Syndromementioning
confidence: 96%
“…Frailty and psychiatric disorders, such as major depressive disorder (MDD) and generalized anxiety disorder (GAD), are thought to be distinct but highly related clinical entities . Evidence suggests that frailty and psychiatric disorders are highly comorbid . A systematic review of evidence exploring comorbidity of frailty and depression found that 4% to 16% of frail adults aged 60 years or older had major depression, with this number rising to 35% in frail older adults aged 75 years or older and in male populations .…”
mentioning
confidence: 99%
“…Only recently have researchers begun to focus on the combined depressed frail phenotype as a high risk, vulnerable population of elders (Figure 1). The purpose of this paper is not to provide a standard review of the relationship between depression and frailty which has been done previously, 15,16 but rather to propose a model for the depressed frail phenotype that elucidates the nature of the association and the potential biological pathways that explain this association, thereby setting a research agenda focused on the assessment and treatment of this high risk phenotype.…”
mentioning
confidence: 99%